2015
DOI: 10.1053/j.ajkd.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Serum Fractalkine (CX3CL1) and Cardiovascular Outcomes and Diabetes: Findings From the Chronic Renal Insufficiency Cohort (CRIC) Study

Abstract: Background Cardiometabolic disease is a major cause of morbidity and mortality in persons with chronic kidney disease (CKD). Fractalkine (CX3CL1) is a potential mediator of both atherosclerosis and metabolic disease. Studies on the relationship of CX3CL1 with risk of CVD events and metabolic traits are lacking, particularly in the high-risk setting of CKD. Study Design Cross-sectional and longitudinal observational analysis. Setting & Participants Adults with CKD from 7 US sites participating in the Chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 35 publications
0
31
1
Order By: Relevance
“…38,40,46 Multiple small studies have examined the association of obesity with the CX3CR1 variants V249I and T280M, demonstrating an association with increased waist circumference, higher levels of HOMA-IR, and a trend towards association with type II DM and metabolic syndrome. 46,47 Despite these prior trends, we did not find any association between common variation in CCR2 , CCR5 or CX3CR1 and any glucometabolic traits in the large GIANT, DIAGRAM, MAGIC, and GLGC GWAS resources.…”
Section: Discussioncontrasting
confidence: 70%
“…38,40,46 Multiple small studies have examined the association of obesity with the CX3CR1 variants V249I and T280M, demonstrating an association with increased waist circumference, higher levels of HOMA-IR, and a trend towards association with type II DM and metabolic syndrome. 46,47 Despite these prior trends, we did not find any association between common variation in CCR2 , CCR5 or CX3CR1 and any glucometabolic traits in the large GIANT, DIAGRAM, MAGIC, and GLGC GWAS resources.…”
Section: Discussioncontrasting
confidence: 70%
“…In line with our findings, upregulation of CX 3 CL1 and CX 3 CR1 has been associated with plaque rupture in patients with unstable angina pectoris. 36 More recently, in a large cohort of patients from the Chronic Renal Insufficiency Cohort (CRIC) study, Shah et al 15 have showed that circulating CX 3 CL1 levels may contribute to both atherosclerosis and diabetes. 15 To our knowledge, our study is the first report showing an association between circulating CX 3 CL1 levels in idiopathic DVT in humans and its potential involvement in subsequent CV events.…”
Section: Discussionmentioning
confidence: 99%
“…11 Among them, fractalkine (CX 3 CL1) is a unique member of the CX 3 C subfamily that exists both as a soluble form, inducing chemotaxis, and as a membrane-bound form on the surface of inflamed endothelium, promoting cell-cell adhesion; in both cases, this involves activation of its cognate receptor CX 3 CR1. 12 Interestingly, circulating CX 3 CL1 has been recently associated with both atherosclerosis 13,14 and diabetes; 15 however, its potential involvement in DVT is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the BMI data of the Chinese population, the Working Group on Obesity of the International Life Science Institute China Office recommended a BMI of 24 kg/m 2 as the cut-off value for overweight and 28 kg/m 2 as the cut-off value for obesity for Chinese [48]. The C-STRIDE cohort and the ROUTE cohort (Japan) [2] had similar BMI, both lower than that in Western studies [35]. Although some reports have suggested higher BMI as an independent risk factor for advanced CKD and CVD [49], the link between BMI and CVD is not clear cut.…”
Section: Discussionmentioning
confidence: 99%